Faktor Risiko Manual Handling dengan Keluhan Nyeri Punggung Bawah Pembuat Batu Bata - Heru Subaris Kasjono; Yamtana Yamtana; Dian Intan Pandini (Jurnal Kesehatan, 2017)
During done manual work handling for objects work hard, it will cause risk of injury or cause musculoskeletal systems. Risk assessment manual work handling with the methods indicators key-Leitmerkmal Method (LMM) intended to know the relationship between time, burden, attitudes of the body, and working conditions manual handling with complaints of the lower back pain at all stages making bricks perceived maker bricks. The kind of research used is surveyed such data is cross sectional. The data taken by lower back pain questionnaire assisted examination physically by nurses and checklist Key-LMM. Analysis relations use the spearman. The results of research acquired at variable time manual handling based frequency raised or operation the transfer of on stage excavation raw materials, the formation and drying bricks there are relations with complaints of  low back pain with p value each are 0,039, 0,047, 0,038 while on the variables of working conditions manual handling in stage excavation raw materials obtained p value of 0,028 with so it can be said there was a correlation between working conditions manual handling with complaints low back pain. A variable load manual handling and attitudes of the body manual handling do not relate in significant to lower back pain all stages making bricks. Conclusion researchers that the variable time manual handling relate in significant with complaints lower back pain in stage excavation raw materials, the formation and drying bricks, while the phase processing raw materials that there was no correlation, in a variable load manual handling and attitudes of the body manual handling all these stage there was no correlation with complaints lower back pain, while variable working conditions manual handling only in stage excavation the raw materials there are relations with complaints lower back pain in the third stage other there was no correlation.